2021
DOI: 10.23960/jak.v26i1.269
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Transfer Pricing, Leverage Dan Profitabilitas Terhadap Tax Avoidance

Abstract: The research aims to examine the effect of transfer pricing, leverage, profitability on tax avoidance. the sample in this study was selected using purposive sampling and obtained 140 samples of companies listed on Indonesia Stock Exchange in 2014- 2019 that met the criteria. The result of hypothesis testing with multiple linear regression analysis using the SPSS 23 application show that transfer pricing has not effect on tax avoidance. leverage and profitability has a significant effext with a negative coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 4 publications
1
2
0
6
Order By: Relevance
“…Because in this study, it is proven that transfer pricing has no effect on tax aggressiveness with the book-tax difference (BTD) proxy. This result of the study aligns with Annisa & Pratomo (2016) and Ellyani & Hudayati (2019), while inconsistent with Panjalusman et al (2018), Ghasani et al (2021), Robin et al (2021), andLaila et al (2021).…”
Section: Effect Of Transfer Pricing On Tax Aggressivenesssupporting
confidence: 72%
See 1 more Smart Citation
“…Because in this study, it is proven that transfer pricing has no effect on tax aggressiveness with the book-tax difference (BTD) proxy. This result of the study aligns with Annisa & Pratomo (2016) and Ellyani & Hudayati (2019), while inconsistent with Panjalusman et al (2018), Ghasani et al (2021), Robin et al (2021), andLaila et al (2021).…”
Section: Effect Of Transfer Pricing On Tax Aggressivenesssupporting
confidence: 72%
“…Several studies have stated that political connections have a positive effect on tax aggressiveness (Adhikari, 2006;Richter et al, 2009;Brown et al, 2015;Kim & Zhang, 2015;Ying et al, 2017;Anggraini & Widarjo, 2020;Sugeng et al, 2020;Sahrir et al, 2021), while there is the study that shown there was no influence of political connections on tax aggressiveness (Giroud, 2013). Study on transfer pricing and tax aggressiveness has also been conducted several times that resulted in transfer pricing having a significant effect on tax avoidance (Annisa & Pratomo, 2016;Ellyani & Hudayati, 2019), while there was a study to prove the effect of transfer pricing on tax avoidance and the result has shown that transfer pricing is having no significant impact on tax avoidance (Panjalusman et al, 2018;Ghasani et al, 2021;Robin et al, 2021;Laila et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Companies do this by shifting high tax collections between corporations with special relationships to countries with lower tax rates. This special relationship is key to the unfair transfer pricing practices that differ from independent firms (Ghasani et al, 2021) . Research that supports this hypothesis is from Lutfia and Pratomo (2018), Marwa and Wahyudi (2018), and Ijlal and Hindria (2021) which states that transfer pricing can have a positive effect on tax avoidance practices because the value of company receivables is large enough so that it has the opportunity to such action.…”
Section: Effect Of Transfer Pricing On Tax Avoidancementioning
confidence: 99%
“…Dan diperoleh 12 perusahaan, sehingga jumlah sampel secara keseluruhan untuk 5 periode adalah sebanyak 60 data. Jika data ploting (titik-titik) yang menujukkan data sesungguhnya membayangi garis diagonal berarti model regresi tersebut berdistribusi normal (Ghasani et al 2021). Pada gambar 2, dapat dilihat bahwa garis diagonal diikuti oleh ploting yang menunjukkan data sesungguhnya tersebut.…”
Section: Metodeunclassified
“…Sehingga disimpulkan bahwa model regresi tersebut berdistribusi normal. Menurut (Ghasani et al 2021) model regresi dinyatakan bebas dari gejala multikolinieritas, jika nilai Tolerance > 0,100 dan nilai VIF < 10,00. Tabel 3 diatas memperlihatkan bahwa nilai Tolerance kedua variabel independen lebih dari 0,100 dan nilai VIF < 10,00.…”
Section: Metodeunclassified